Quantitative High Performance Thin-Layer Chromatography Method for Analysis of Vitexin and Isovitexin in Extracts of Leaves of Ficus deltoidea - Shafaei, Armaghan; Farsi, Elham; Ismail, Zhari; Z. Asmawi, Moh (Asian Journal of Chemistry, 2012)
The present study aimed to develop and validate a single step, simple, sensitive and accurate high performance thin-layer chromatography (HPTLC) method for quantification of vitexin and isovitexin in extracts of Ficus deltoidea. The method employed TLC plates as stationary phase with mobile phase as ethyl acetate:formic acid:acetic acid:water (100:11:11: 26). The method had shown linearity in a range of 0.1-300 μg/mL with correlation coefficient of R2 = 0.988, 0.986 and 0.985, 0.982 with respective to peak area and height for vitexin and isovitexin, respectively. Recovery and accuracy (intra and inter day) values were found to be 92.10-101.98, 93.56-103.64 and 99.99-105.20 %, respectively with relative standard deviation (RSD) less than 5. Lowest limit of detection (LOD) and lowest limit of quantification (LOQ) were found to be 0.1 and 1.0 μg, respectively. Results of this study indicate that the proposed method is simple, sensitive, accurate and precise.